2006
DOI: 10.1016/j.euroneuro.2006.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The Montgomery Äsberg and the Hamilton ratings of depression: A comparison of measures

Abstract: The 17-item Hamilton Rating Scale for Depression (HRSD 17 ) and the Montgomery Äsberg Depression Rating Scale (MADRS) are two widely used clinicianrated symptom scales. A 6-item version of the HRSD (HRSD 6 ) was created by Bech to address the psychometric limitations of the HRSD 17 . The psychometric properties of these measures were compared using classical test theory (CTT) and item response theory (IRT) methods. IRT methods were used to equate total scores on any two scales. Data from two distinctly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 50 publications
7
136
1
6
Order By: Relevance
“…30,32 The MADRS is a valid and reliable unifactorial depression rating scale 30,33,34 and has high internal consistency with Cronbach's alpha values of 0.85-0.92 in patients with major depressive disorder and stroke. 35,36 In our study the Cronbach's alpha coefficient was 0.86. In comparison to other measurements the MADRS has the strongest association to the clinician's assessment.…”
Section: Screening Questions (Sq-3)mentioning
confidence: 43%
“…30,32 The MADRS is a valid and reliable unifactorial depression rating scale 30,33,34 and has high internal consistency with Cronbach's alpha values of 0.85-0.92 in patients with major depressive disorder and stroke. 35,36 In our study the Cronbach's alpha coefficient was 0.86. In comparison to other measurements the MADRS has the strongest association to the clinician's assessment.…”
Section: Screening Questions (Sq-3)mentioning
confidence: 43%
“…Exit scores are typically preferable to baseline scores because the study enrollment criteria may result in a reduction in the variability of the baseline scores and may have been used in other studies on the psychometric properties of depression measures. [35][36][37] This effect may be magnified in the present study because a minimum baseline score on the HRSD 17 was part of the inclusion criteria.…”
Section: Statistical Analysesmentioning
confidence: 88%
“…Remission ' was defined by a consensus board as a score of f7 on HAMD 17 or f8 on BDI (Frank et al 1991). There has been some debate over the thresholds for remission on MADRS : a threshold of f11 was first suggested, but later investigations found that a MADRS total score of 10 or 9 better corresponds to the HAMD 17 score of 7 (Zimmerman et al 2004 ;Carmody et al 2006 ;Uher et al 2008). Therefore, we define ' remission ' as reaching a score of f7 on HAMD 17 , f10 on MADRS and f8 on BDI, based on the last valid observation over the 12-weeks, i.e.…”
Section: Measures Of Depressive Symptomsmentioning
confidence: 99%